Laba-Laba Pembuat Jaring Di Lahan Areal Tanaman Padi Dan Sekitarnya Di Kabupaten Minahasa - Fander Juan. Hosang (Universitas Sam Ratulangi, 2018)
Abstract Spiders is one of the dominant predator or natural enemies classified in arthropod groups that play an important role in agricultural ecosystems, especially paddy field plantations. This study aimed to determine the types and populations of spider, especially net-spider in the area of rice fields and its surrounding. This research was conducted in 3 (three) different villages namely Sendangan Village Sonder District, Winebetan South Langowan District, and Koyawas West Langowan District for 3 months started on August to October 2017. This research was conducted by survey method. Sampling was carried out on spider webs found in embankments, ridge edges and areas surround the rice fields. Observations are conducted every 2 weeks for 3 months. The results showed that there were 224 individuals consisting of 13 species and 5 families of spiders divided into five family i.e. Tetragnathidae, Araneidae, Salticidae, Theriidae and Mitidae. The highest spider population was found in the location of the Koyawas Village (124 individuals), followed by Sendangan Village (64 individuals) and the lowest in Winebetan Village (35 individuals). In addition to that, the most populated rice fields in relation to the age of the plant was at the age of 8 Weeks After Planting (MTS) with the most dominant spider found in the location of Koyawas West Subdistrict, classified as Family Tetragnathidae 95 Individuals (in total), consisting of genus / species T. vermiformis, T. virescens, T.javana, T. nitens and the lowest is family Salticidae which is of genus / species Plexppus species which are only two individuals.